2017
DOI: 10.1002/uog.15938
|View full text |Cite
|
Sign up to set email alerts
|

Uteroplacental Doppler flow and pregnancy outcome in women with tetralogy of Fallot

Abstract: The majority of women with surgically corrected ToF tolerate pregnancy well. However, UDF indices are more frequently abnormal in these women, suggesting impaired placentation. The association of impaired right ventricular function parameters with abnormal UDF suggests that cardiac dysfunction contributes to defective placentation or placental perfusion mismatch and may explain the increased incidence of obstetric and neonatal complications. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 42 publications
4
20
1
Order By: Relevance
“…These findings suggest that impaired RV function might be a predisposing factor for poor placental function, which is known to be associated with adverse maternal and neonatal outcome. The current study combining CMR with PI confirms our previous findings that pre-existing reduced RV function is associated with impaired uteroplacental circulation [1,[12][13][14]. In our previous echocardiographic studies, we were limited in the assessment of RV function and CO measurements due to the specific modality.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These findings suggest that impaired RV function might be a predisposing factor for poor placental function, which is known to be associated with adverse maternal and neonatal outcome. The current study combining CMR with PI confirms our previous findings that pre-existing reduced RV function is associated with impaired uteroplacental circulation [1,[12][13][14]. In our previous echocardiographic studies, we were limited in the assessment of RV function and CO measurements due to the specific modality.…”
Section: Discussionsupporting
confidence: 84%
“…In the ZAHARA II and III study 66 repaired ToF women were included. For the present study, women were excluded because of miscarriage (n = 3), no CMR evaluation available because of a pacemaker (n = 3) or no CMR evaluation available within 2 years before pregnancy (n = 29), resulting in a total study population of 31 repaired ToF women (median time between the CMR evaluation and date of conception was 8 [3][4][5][6][7][8][9][10][11][12][13][14] months).…”
Section: Pre-pregnancy Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we occasionally encountered that women with uncorrected TOF got pregnant. Due to the extra cardiac load during pregnancy, women with uncorrected TOF had much higher maternal and perinatal morbidity compared to general population [1][2][3][4][5]9]. These cases are relatively rare and almost all of published studies for these patients in the literature were case reports.…”
Section: Discussionmentioning
confidence: 99%
“…But it is generally known that heart disease constitutes a leading nonobstetric cause of maternal mortality especially in patients with those cyanotic and complex shunt lesions [4]. Previous studies on pregnant women with TOF showed that pregnancy carries a considerable risk to the women's status, and the adverse cardiovascular events may be associated with right ventricular dysfunction, severe pulmonary hypertension, and severe pulmonic regurgitation with RV dysfunction [10,11]. Right ventricular function parameters with abnormal uteroplacental Doppler flow (UDF) suggests that cardiac dysfunction contributes to defective placentation or placental perfusion mismatch and may explain the increased incidence of obstetric and neonatal complications [11].…”
Section: Discussionmentioning
confidence: 99%